Reconnecting the wetlands through non-discrete architecture - Rahman, Aulia (ARSNET, 2025)
This design study explores non-discrete architecture as a form of architecture that connects nature and the built environment. Architecture often separates itself and its users from the natural setting, leading to environmental neglect and the gradual loss ofthe natural environment. The idea of non-discrete architecture focuses on how the relationship between humans and nature can be reconstructed by creating spatial layers that can actively participate in living processes. This study focuses on the neglected wetland environment in Banjarmasin, South Kalimantan. The inquiry begins by documenting the various experiences of nature in the area, from the abundance presence of wilderness and the dynamic water reflections of the wetlands. The study explores how such experience is captured through spatial boundaries such as roof structures and floor gaps. This study develops a form of low-tech pavilion that reconsiders the boundaries and how it is situated amidst the wetland landscapes. The project aims to bring a connection between the inside and the outside and captures the landscape dynamics, creating an animated interior of the space. In doing so, it fosters awareness of environmental beauty and renews appreciation for the wetland architecture that has been neglected.